High Hidden Burden of Diabetes Mellitus among Adults Aged 18 Years and Above in Urban Northwest Ethiopia. (23rd November 2020) - Wolde, Haileab Fekadu; Derso, Terefe; Biks, Gashaw Andargie; Yitayal, Mezgebu; Ayele, Tadesse Awoke; Gelaye, Kassahun Alemu; Demissie, Getu Debalkie; Azale, Telake; Misganaw, Bisrat; Kebede, Adane; Teshome, Destaw Fetene; Dellie, Endalkachew; et al.
Abstract : Background . Ethiopia is one of the sub-Saharan African countries with a rapidly increasing burden of diabetes mellitus (DM). There is limited updated information about the community-based burden of the disease and its associated factors in Ethiopia which is very crucial to plan effective prevention and control measures against the disease. This study is aimed at determining the burden of DM and its associated factors in urban northwest Ethiopia. Methods . A community-based cross-sectional study was conducted from April to May 2019 among residents aged ≥ 18 years in Gondar town and urban kebeles (lowest administrative units of the country) of Health and Demographic Surveillance System site (HDSS) in Dabat district. A multistage sampling technique was used to select 773 participants. World Health Organization (WHO) stepwise approach for noncommunicable disease surveillance was used to collect the data. Fasting blood glucose FBS ≥ 126   mg / dl was used to diagnose DM. Descriptive statistics were done to describe the variables of the study. Prevalence with its 95% confidence interval (CI) was estimated. Binary logistic regression model was fitted, variables with p value < 0.05 were considered to have a significant association with the outcome, and odds ratio (OR) was used to measure the strength of association. Result . Of the total participants, 6.34% (95% CI; 4.82, 8.29) were found to be diabetic. Of these, 40 (81.6%) were newly diagnosed. Besides, the prevalence of prediabetes was 9.31% (95% CI: 7.45, 11.58). Increased age (AOR = 1.06, 95% CI; 1.04, 1.09) and eating vegetables one to three days per week (AOR =0.29, 95% CI; 0.13, 0.65) were significantly associated with diabetes. Conclusion . The overall prevalence of DM is a bit higher than the national estimate, while the proportion of undiagnosed DM which can easily progress to disabling and life-threatening complications was alarmingly high. Age and frequency of eating vegetables per week were associated with diabetes. In light of this finding, future prevention and control measures against the diseases should consider the identified factors. There should also be improved access to screening services.